Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1108/vjikms-03-2022-0083
|View full text |Cite
|
Sign up to set email alerts
|

The influence of humble leadership on employees’ work engagement: the mediating role of leader knowledge-sharing behaviour

Abstract: Purpose This paper empirically aims to investigate the mediating role of leader knowledge-sharing behaviour (LKSB) in the relationship between humble leadership (HL) and work engagement (WE). Design/methodology/approach The responses of 321 employees in hospitality organisations in Jordan were collected via an online survey. The study data was then analysed using structural equation modelling. Findings The study found that leaders showing humble behaviour were able to share knowledge that ultimately improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 66 publications
1
8
0
3
Order By: Relevance
“…Relational leaders respect employees' opinions in decision-making and share valued resources which could promote employee creativity (Mo et al , 2019). This study enriches and advances previous studies on job embeddedness and dedication (Akgunduz et al, 2022), work engagement (Al Hawamdeh, 2022; Vakira et al, 2022) and civic virtue behaviour (Khan et al, 2020). Finally, this study revealed the mediating role of knowledge-sharing behaviour on the link between relational leadership and employee creativity, thus indicating how relational leadership behaviours transfers to employees' creative behaviour.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Relational leaders respect employees' opinions in decision-making and share valued resources which could promote employee creativity (Mo et al , 2019). This study enriches and advances previous studies on job embeddedness and dedication (Akgunduz et al, 2022), work engagement (Al Hawamdeh, 2022; Vakira et al, 2022) and civic virtue behaviour (Khan et al, 2020). Finally, this study revealed the mediating role of knowledge-sharing behaviour on the link between relational leadership and employee creativity, thus indicating how relational leadership behaviours transfers to employees' creative behaviour.…”
Section: Discussionsupporting
confidence: 80%
“…Thus, we reasoned that leaders who build positive relationships with employees, through knowledge-sharing behaviour, will engender greater felt obligation on the part of employees to be creative because knowledge is a cherished resource employees use in building their competencies at work (Liu et al, 2010). Leaders' knowledge-sharing behaviour has been acknowledged as being among some of the important determinants of hotel efficiency and improvement given the influence it has on employee creativity (Al Hawamdeh, 2022). Consequently, using the principles of social exchange theory, this study investigates the association among relational leadership, knowledge-sharing behaviour, leader–follower tenure and employee creativity.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, leaders must actively share knowledge and respond to requests for knowledge from others, as their followers will observe, learn, internalise and then imitate their actions. The key to minimising the likelihood of employees not sharing knowledge – and thereby preventing them from engaging in knowledge-hiding behaviour – is to exercise humble leadership (Al Hawamdeh, 2022). Secondly, this study reveals how humble leadership mitigates knowledge-hiding behaviour in health-care organisations in developing countries, such as Jordan.…”
Section: Discussionmentioning
confidence: 99%
“…HL has been previously associated with different employee outcomes [67,68]. HL can significantly foster the WREN level of employees [69]. We use the definition by Kahn [70] to conceptualise WE.…”
Section: Theory and Hypothesesmentioning
confidence: 99%